Meditation über Humor und Christentum: Für Klaus-Peter Jörns zum 60. Geburtstag - Hübner, Kurt (Zeitschrift für Theologie und Kirche, 1999)
In the Christian view, humor is rooted in the belief in the vanity and the futility of the world and the fact that these can be overcome by the goodness of love. Thus the joy which it evokes reflects the joy of the kerygma.